What Factors Are Associated With Response Rates for Long-term Follow-up Questionnaire Studies in Hand Surgery?. Issue 12 (December 2020) - Westenberg, Ritsaart F.; Nierich, Juliette; Lans, Jonathan; Garg, Rohit; Eberlin, Kyle R.; Chen, Neal C.
Abstract: Background: Long-term follow-up studies are an important tool in the evaluation of orthopaedic illness and its treatment options. However, a patient's participation in a follow-up study may be affected by several factors, leading to variability in response rates and the risk of selection bias. Questions/purposes: (1) What is the average response rate in hand surgery questionnaire studies? (2) What factors are associated with higher and lower response rates to research questionnaires? (3) What factors are associated with higher and lower contact, initial participation, and completion rates? Methods: We included 798 adult patients who were enrolled in one of 12 questionnaire follow-up studies in the hand and upper extremity service of our institution. All included studies evaluated patient-reported outcomes for the surgical treatment of upper extremity conditions using questionnaires and all used the same enrollment design. Patients were invited by letter to ask if they would be willing to participate, and we informed them that they would be contacted by telephone at least three times if they did not respond to the letter. Patients were contacted at a median of 6.6 years (interquartile range [IQR] 3.7 to 11) after surgery. The successful response rate was 49% (390 of 798 patients). We manually reviewed records to collect data on patient characteristics, and we performed bivariate analysis and multivariable logistic regression analysis to identify factors associated with the contact rate (percentage of patients reached by either mail, phone, or email), initial response rate (percentage of reached patients who initiated participation), completion rate (percentage of patients who initiated participation and completed the entire follow-up questionnaire), and our primary outcome successful response rate (percentage of patients who were contacted and who completed the entire questionnaire). Results: The average response rate in hand surgery questionnaire studies was 49% (390 of 798 patients). In the multivariable analysis, enrollment of women (odds ratio 1.43 [95% confidence interval 1.03 to 1.97]; p = 0.031) was independently associated with higher response rates. On the contrary, a longer follow-up time from surgery (OR 0.95; 95% CI 0.92 to 0.99]; p = 0.015) and multiple researchers contacting patients (OR 0.51 [95% CI 0.37 to 0.71]; p < 0.001) were independently associated with lower response rates. The contact rate was higher for women (OR 1.46 [95% CI 1.03 to 2.06]; p = 0.034) and patients with higher income (OR 1.000007 [95% CI 1.000001 to 1.000013]; p = 0.019). The contact rate was lower in patients with a longer follow-up time from surgery (OR 0.93 [95% CI 0.90 to 0.97]; p = 0.001). The initial participation rate was lower when patients were contacted by multiple researchers (OR: 0.34 [95% CI 0.23 to 0.52]; p < 0.001). Studies with a lower number of questions (36; IQR 22 to 46) were completed more frequently than studies with a higher number of questions (51; IQR 39 to 67; p = 0.044). Conclusions: Studies assessing long-term outcomes that have a large proportion of men and longer follow-up time tend to have lower response rates. When performing a follow-up study, it seems beneficial to have one researcher contact the patients and use a shorter questionnaire. Results of this study can help clarify the response rates in hand surgery follow-up questionnaire studies and help with the planning of future follow-up studies. Level of Evidence: Level II, prognostic study.